Latency Analysis in Real LTE Networks for Vehicular Applications - Andrade, Hilson G. Vilar De; Ferreira, Caio C. L. L.; Silva Filho, Abel G. Da (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2016)
In the development path to implement V2X (Vehicle-to-Vehicle and Vehicle-to-Infrastructure) communications, two different, but not entirely concurrent approaches, are been investigated: the use of a new technology standard, 802.11p, denoted as DSRC/WAVE (Dedicated Short Range Communications/Wireless Access in Vehicular Environments), and the use of an already established technology, UMTS/LTE (Universal Mobile Communications System/Long Term Evolution). The choice to invest in one of these two technologies to build a V2X infrastructure passes through which one will provide a minor latency communication time between network nodes. This paper presents a measure of this parameter in mobile networks of real mobile service providers, distinguishing between data obtained from UMTS and LTE servers. Furthermore, is presented an architecture where the smartphone is a gateway to provide V2X communications, in regards that this device has a widespread adoption and can in rapidly pace turn the car a node in the Internet of Things.